Generación morfológica digital en arquitectura: diseño paramétrico y algoritmos evolucionistas - Barrionuevo, Luis F. (2018)
This paper presents results obtained from a research project development carried out in the Design Systems Laboratory, FAU-UNT. This research was oriented to establish techniques and procedures for the production of potentially architectural 3D objects, during conceptual stage. Objects with different scales, feasible to accept architecture, were studied. For their generation, visual programming environments oriented to parametric design, were applied. Parameters, as genomes, were put to work in an "evolutionary algorithm" environment with the purpose to obtain architectural design applications, emulating biological evolutions. The main procedure consists in testing quantitative and qualitative parameters that define each object, until an expected architectural result is reached. Some results obtained are shown.